STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KUALITAS SHALAT BERJAMAAH DI SDN 106162 MEDAN STATE KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Nurtakyidah Nurtakyidah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
In general, the purpose of this study is to describe the strategy of Islamic Education teachers in improving the quality of prayer in congregation at SDN 106162 Medan Estate Percut Sei Tuan District Deli Serdang Regency. The research findings based on the observation instruments, interviews and documentation studies showed that: First, the process of congregational prayer was carried out with the guidance and direction of the Islamic Education teachers. Second, the coordination between the headmaster, the Islamic Education Teachers, and students’ parents in improving the quality of prayer in congregation at SDN 106162 Medan Estate Percut Sei Tuan District Deli Serdang Regency is through formal as well as informal meetings. Third, the approach used by the Islamic Education teachers in motivating students to improve the quality of prayer in congregation at SDN 106162 Medan Estate Percut Sei Tuan District Deli Serdang Regency is through religious, individual, and group approaches. Fourth, the obstacles and challenges faced by the Islamic Education teachers in improvingthe quality of prayer in congregation at SDN 106162 Medan Estate PercutSei Tuan District Deli Serdang Regency.